Evaluation of Maize Genotypes for Resistance against Gray Leaf Spot In Hills of Nepal - Rijal, Tirtha Raj; Shrestha, Jiban; Acharya, Bashistha; Dhami, Narayan Bahadur; Karki, Ajay; Aryal, Ambika; Hamal, Pratik (International Journal of Applied Sciences and Biotechnology, 2015)
Maize crop is affected by several diseases, but Gray leaf spot (GLS), is the major disease that threat maize production in every year in mid-hills and high-hills of Nepal. To identify the source of resistant on gray leaf spot disease maize genotypes were screened/evaluated under hot spots during 2013 and 2014 summer seasons across the hill environment of Nepal. In the screening nursery both exotic(CIMMYT China) and NMRP developed genotypes were included and screened at Pakhribas, Dhungkharka, Supping and Salyan during 2013 & 2014 summer seasons under replicated conditions. The genotypes identified resistant and high yielding at Dhungkharka in 2013 were YML58/(CML226/CATETO//CML226/CATETO)F2-B-1-2-B,YML32/(P147-F2-108-S7/P45-C8-76-S5)-F2-B-30-1-3, YML32/Cel FSRYS9956-B-3-2-4-B and YML58/(G34/36/G33TSR)-F2-B-4-1-B. In case of Salyan none of the genotypes showed resistant reaction against GLS but eight genotypes namely; YML23/P502-C2-58-1-1-2-5-B, YML23/P502-C2-185-3-4-1-3-B-1-B, YML23/P502-C3-F2-10-8-1-1-B, YML23/GLSI01P502-B-25-2-B, YML23/MBR-C5W-F108-2-3-1-B, YS12Q-189, YS12Q-33 and YS12Q-189 reacted MR reaction. At Pakhribas two genotypes reacted resistant (R) reaction namely; YML23/GLS101HGA-B-4-1-B and YS12Q-189 and other ten genotypes responded MR reaction. None of the tested entries at Suping responded resistant reaction but four genotypes ZM-401, 07SADVI, ZM-627 and BGBYPOP responded MR reaction against GLS. During 2014 summer season a total of 20 genotypes both exotic (CIMMYT India) and NMRP developed were screened against GLS across the hill regions of Pakhribas, Dhungkharka and Salyan. From the result of Pakhribas the genotype P501SRCO/P502SRCO was recorded for resistant (1.3) reaction and three genotypes 05SADVI, Entry # 36 and Entry # 27 were responded for MR reaction. In case of Dhungkharka nine genotypes namely; ZM-401, ZM-627, 05SADVI, 07SADVI, TLBRSO7F16, ENTRY#33, ENTRY#24, ENTRY#32 and ENTRY#21 were recorded for MR reaction. The tested genotypes at Salyan revealed that six genotypes namely; 05SADVI, 07SADVI, ACROSS-9942/ACROSS-9944, BGBYPOP, ENTRY # 24 and ENTRY# 32 were reacted resistant reaction and the genotype 07SADVI produced significantly highest grain yield (8638 kg/ha). Int J Appl Sci Biotechnol, Vol 3(3): 504-512